Overexpression of the protein disulfide isomerase AtCYO1 in chloroplasts slows dark-induced senescence in Arabidopsis - Tominaga, Jun (BMC Plant Biol, 2018)
BACKGROUND: Chlorophyll breakdown is the most obvious sign of leaf senescence. The chlorophyll catabolism pathway and the associated proteins/genes have been identified in considerable detail by genetic approaches combined with stay-green phenotyping. Arabidopsis CYO1 (AtCYO1), a protein disulfide reductase/isomerase localized in the thylakoid membrane, is hypothesized to assemble the photosystem by interacting with cysteine residues of the subunits. RESULTS: In this study, we report that ectopic overexpression of AtCYO1 in leaves induces a stay-green phenotype during darkness, where oxidative conditions favor catabolism. In AtCYO1ox leaves, Fv/Fm and both chlorophyll a and chlorophyll b content remained high during dark-induced senescence. The thylakoid ultrastructure was preserved for a longer time in AtCYO1ox leaves than in wild type leaves. AtCYO1ox leaves maintained thylakoid chlorophyll-binding proteins associated with both PSII (D1, D2, CP43, CP47, LHCB2, and Cyt f) and PSI (PSA-A/B), as well as stromal proteins (Rubisco and ferredoxin-NADP+ reductase). AtCYO1ox did not affect senescence-inducible gene expression for chlorophyll catabolism or accumulation of chlorophyll catabolites. CONCLUSIONS: Our results suggest that ectopic overexpression of AtCYO1 had a negative impact on the initiation of chlorophyll degradation and proteolysis within chloroplasts. Our findings cast new light on the redox regulation of protein disulfide bonds for the maintenance of functional chloroplasts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1294-5) contains supplementary material, which is available to authorized users.